Geometric analysis of variable ratio steering gear. (5th August 2014) - Yanai, T.; Hitomi, N.; Higuchi, M.
This paper examines the geometric relationships between the rack and pinion (sector) gears which compose a variable ratio steering gear, and investigates a universal method for analyzing these gear teeth surfaces. The proposed analytical method was applied to an investigation of a ball and screw type steering system. Various geometric characteristics of the sector tooth surface generated by the plane rack tooth surface were studied. Tooth design characteristics such as undercut limit and tooth profile interference were obtained.